IMPLEMENTASI IBADAH HAJI DALAM KEHIDUPAN (STUDI KASUS DI KOTA TEGAL) - Fajar Dian Aryani; Basukiyatno Basukiyatno; Yana Mulyana (LPPM Universitas Pekalongan, 2016)
Hajj is not the monopoly of the rich, rank, or officials. Hajj is the prerogative of God calling people the choice to be his guest of honor. For Indonesia, today to be the guest of honor God must wait until about twenty years. A very rare opportunity to be a guest of God, a long wait time, huge cost, the sacrifice of time, effort and everything, make the pilgrimage worth very mulya and expensive (exclusive). They were going to Hajj should be prepared carefully, orderly and mature so that Hajj mabrur and deserve a reply heaven. In accordance with the formulation of the problem, the purpose of this research to get answers to the following issues; Changes in a person's behavior after doing hajj., The positive impact of changes in the person's behavior after doing hajj., Positive impact on the environment of a person after doing Hajj. The Hajj will be the motivation to improve. Someone who is steeped in sin, often desperate due to his sins. With the assurance of God that Haji will remove sin, as if we were refreshed, so it will be motivated to keep themselves in order not to sin again. Each person generally will gain wisdom and experience itself that should be told to others as a sense of gratitude and a lesson for others. Who knows may be wasilah that others follow the lead of the pilgrimage. But if there is less good experience, enough saved for introspection, even if told not to frighten but to maintain vigilance. Although Haram in full condition, if you want to thawaf near the Ka'aba, be sure and ask, God willing, we will get close to the Kaaba. Descriptive qualitative research methods. Collecting data with observations on draft interview. Respondents pilgrims joined in some KBIH. The results showed that; 1) Implementation of the pilgrimage could fundamentally alter the behavior of the person, 2) changes in the level of personal value, in the form of obedience to God Allah, 3) Changes in the level of environmental and sociological value, such as; humanism, social solidarity, tolerance, mutual help.